# Series expansion $(1-\cos{x})^{-1}$

How do i get the series expansion $(1-\cos{x})^{-1} = \frac{2}{x^2}+\frac{1}{6}+\frac{x^2}{120}+o(x^4)$ ?

-
Do you know the (beginning of the) series expansion of cosine at zero? – Did Mar 19 '13 at 11:56
What is your background, and what do you know already?Thanks in advance still. – awllower Mar 19 '13 at 12:15

$$\frac{1}{1 - x} = 1 + x + x^2 + O(x^3)$$

and so

$$\frac{1}{1 - \cos x}= \frac{1}{\frac{x^2}{2} - \frac{x^4}{24} + \frac{x^6}{6!}} = \frac{2}{x^2} \frac{1}{1 - (\frac{x^2}{12} - \frac{x^4}{360} + O(x^6))}$$ $$= \frac{2}{x^2} \left( 1 + \left(\frac{x^2}{12} - \frac{x^4}{360}\right) + \frac{x^4}{144} + O(x^6) \right) = \frac{2}{x^2} + \frac{1}{6} + \frac{x^2}{120} + O(x^4)$$

-

\begin{align} \frac{1}{1 - \cos x} &= \left(\frac{x^2}{2} - \frac{x^4}{24} + \frac{x^6}{720} + o(x^6)\right)^{-1}\\ & = \frac{2}{x^2}\left(1-\frac{x^2}{12} + \frac{x^4}{360} + o(x^4)\right)^{-1}\\ & = \frac{2}{x^2}\left(1 + \frac{x^2}{12} - \frac{x^4}{360} + \frac{x^4}{144} + o(x^4)\right)\\ & = \frac{2}{x^2} + \frac{1}{6} + \frac{x^2}{120} + o(x^2) \end{align}

-

Can help this: $(1-\cos{x})^{-1} = \dfrac{1}{2\sin^2{\dfrac{x}{2}}}=-\dfrac{d}{dx}\left(\cot{\dfrac{x}{2}}\right)?$

-